Research on Tax Debt Collection: A Literature Review - Romy Sukma Bangsa; Milla Sepliana Setyowati (Eduvest - Journal of Universal Studies, 2025)
The Audit Board's audit reports from 2021 to 2023 consistently reveal suboptimal tax debt collection implementation in Indonesia, with policies stagnating for over 20 years. This highlights the need to evaluate Indonesia's tax collection law based on recent research. However, research on tax debt collection is relatively limited, and an understanding of the research development in related topics is not yet available. Through a literature review and thematic analysis, the authors identified six research themes related to tax debt collection: "Causes of Tax Arrears," "The Government as a Tax Creditor," "Tax Debt Collection Strategies," "Protection of Tax Delinquent's Rights," "Utilization of Information Systems and Technology in Tax Debt Collection," and "Tax Delinquent's Reactions to Tax Debt Collection Measures." The mapping of these themes can guide future research or policy improvements related to tax debt collection that are needed in Indonesia.